Digitalisasi Produk dan Layanan UMKM sebagai Upaya Pengembangan Destinasi Wisata Setu Babakan, Jakarta Selatan - Nabila Rahmawati; Nayra Faziela Putri Dinanti; Nayyara Muhayya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the role of digitalizing micro, small, and medium enterprises (MSMEs) products and services in supporting the development of Setu Babakan as a cultural tourism destination in South Jakarta. The background of this research is the increasing demand for digital-based tourism services alongside the limited digital adoption among cultural-based MSMEs. The objective of this study is to analyze the extent, dynamics, and implications of digitalization implemented by MSMEs in Setu Babakan. This research employs a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation. The findings reveal that digitalization contributes positively to expanding promotional reach, improving transaction convenience through non-cash payments, and strengthening destination attractiveness. However, digital adoption remains uneven due to limitations in digital literacy, infrastructure, and continuous assistance. The study implies that integrated digital strategies and sustained stakeholder collaboration are essential to enhance MSME resilience and support sustainable cultural tourism development.